THE JUXTAPOSITION OF IMAGES AND THE PERSPECTIVE OF THE MIGRANT SUBJECT IN 5 METROS DE POEMAS (1927) BY CARLOS OQUENDO DE AMAT - Durand Luna, Sandra Melina (2022)
The Peruvian vanguard was a period characterized by linguistic experimentation and the development of visual poetry that invites the reader to actively participate in the interpretation of the poem. Carlos Oquendo de Amat (1905-1936) is one of the greatest representatives of the new sensibility that is expressed through language and sets a trend in twentieth-century Peruvian poetry. For this reason, this article proposes to examine, based on the theory of modern versology by Isabel Paraíso and Francisco López Estrada, the juxtaposition of images in the collection of poems 5 meters of poems (1927) to explore the relationship between the visual aspect and semantic from the perspective of the migrant subject to the modernization of the city, technological advances and the media.